SUBJECT INDEXING IN LIBRARY ENVIRONMENT: CHALLENGES AND PROSPECTS (Perspectivas em Ciência da Informação, 2011)
At present the assignment of subject descriptors or indexing the content of books is not always associated to the specific context of each library, resulting in many cases the retrieval of materials is not appropriate. This paper analyzes the main challenges and prospects for the indexing of books, progress in the analysis of materials in library catalogs, reviews the procedures, instruments, rules and behaviors used in the analysis and representation of the contents of books. It also shows the interaction between teaching, research and performance necessary for students to develop skills in analysis, representation and information retrieval, and the principles-perhaps less obvious of knowledge organization. The study shows that the policies of management information, more quantitative than qualitative leave in the background intellectual processing content thus impairing the retrieval of materials through the library catalog. Finally, the proposal contains a number of teaching materials related to the descriptors allocation in library contexts.